Is the Filioque an Obstacle to a Pneumatologically Robust Christology?: A Response from Reformed Resources - Kieser, Ty (Journal of reformed theology, 2018)
This article provides examples of pneumatologically robust Reformed Christologies that are founded upon the doctrine of the filioque, as counter-evidence against the charge that the filioque prohibits the possibility of a Spirit Christology.' In order to provide this evidence, four Reformed theologians from four centuries (Calvin, Owen, Edwards, and Bavinck) are surveyed, particularly as they articulate the doctrine of the filioque and its significance for the role of the Holy Spirit in their Christologies. The article concludes that, rather than constituting an obstacle to a pneumatologically robust Christology, the filioque can positively contribute to a genuine Spirit Christology.